The instruments of monetary policy in the countries of the European Economic Community - European Economic Community ([n. p., Pub. Services of the European Communities, 1962)
This contains a study of the instruments of monetary policy in the member states of the European Economic Commission. The report is used as a basic document in detailed discussions of the nature, use and effectiveness of instruments of monetary policy among the members countries.
Cover title.
At head of title: European Economic Community.
usc 25/07/2017
Loans
Keywords: Monetary policy; Europe--European Economic Community countries